Complement Has Brains—Do Intracellular Complement and Immunometabolism Cooperate in Tissue Homeostasis and Behavior? - Kunz, Natalia; Kemper, Claudia (Frontiers in Immunology, 2021)
The classical liver-derived and serum-effective complement system is well appreciated as a key mediator of host protection via instruction of innate and adaptive immunity. However, recent studies have discovered an intracellularly active complement system, the complosome, which has emerged as a central regulator of the core metabolic pathways fueling human immune cell activity. Induction of expression of components of the complosome, particularly complement component C3, during transmigration from the circulation into peripheral tissues is a defining characteristic of monocytes and T cells in tissues. Intracellular complement activity is required to induce metabolic reprogramming of immune cells, including increased glycolytic flux and OXPHOS, which drive the production of the pro-inflammatory cytokine IFN-gamma. Consequently, reduced complosome activity translates into defects in normal monocyte activation, faulty Th1 and cytotoxic T lymphocyte responses and loss of protective tissue immunity. Intriguingly, neurological research has identified an unexpected connection between the physiological presence of innate and adaptive immune cells and certain cytokines, including IFN-gamma, in and around the brain and normal brain function. In this opinion piece, we will first review the current state of research regarding complement driven metabolic reprogramming in the context of immune cell tissue entry and residency. We will then discuss how published work on the role of IFN-gamma and T cells in the brain support a hypothesis that an evolutionarily conserved cooperation between the complosome, cell metabolism and IFN-gamma regulates organismal behavior, as well as immunity.